أحكام بيع العربون بين الفقه الإسلامي والقانون الوضعي - قحمص, حسين (University of eloued جامعة الوادي, 2016)
يعالج ىذا البحث موضوع العربون بين الفقو الإسلامي والقانون الوضعي والعربون يعتبر من أىم البيوع المتداولة بين الناس في القديم والحديث حيث حاولت من خلال ىذه الد ارسة بيان المقصود بالعربون, والاختلاف بين الفقياء حول مشروعيتو, وبيان أن الرأي الذي رجحو غالبية الفقياء المعاصرين, والذي يدعمو الواقع ىو الجواز, وكذلك تطرقت الدراسة إلي دخول العربون في كثير من العقود والتطبيقات المالية المعاصرة, وما مديجواز ذلك, ىذا كمو مع مقارنتو بالفقو القانوني كمما أمكن This research deals with the subject of earnest mone between Islamic jurisprudence and positive law and t deposit is considered one of the most important sale circulating among people in ancient and modern, so tried through this study intended to release the depo and differences between scholars about its legitimacy and a statement that the opinion, which favored by th majority of contemporary jurists, and which is supported by fact passport, and also touched on the study to the entry of earnest money in many of the contemporary financial contracts and applications, an how passport, this whole compared with the jurisprudence whenever possible.
شريعة وقانون
Keywords: بيع العربون/الفقه الإسلامي/القانون الوضعي; Custody/Sharia/Provisions